Penanganan Susut Panen dan Pasca Panen Padi Kaitannya dengan Anomali Iklim di Wilayah Daerah Istimewa Yogyakarta - Mahargono Kobarsih; Nugroho Siswanto (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2015)
To reduced losses in rice farming requires the application of modern agricultural machinery in harvesting equipment, postharvest and processing. Varying knowledge of farmers and entrepreneur rice milling unit (RMU) in yield loss as well as the impacts of global climate change research should be conducted through a structured survey of farmers and entrepreneurs RMU in Yogyakarta. Results obtained demonstrate the preferred use of new type variety among farmers so that the tool is suitable harvest sickle cutting down system in districts of Bantul and Gunungkidul more popular as straw used for animal feed. More than 70% of farmers do at harvest time by looking at the panicle and leaf color. Utilization of power threshers more developed in Sleman because of such preferred cut up and threshing by stampede way. With the limitations of manpower, the farmer was forced to delay harvest in Gunungkidul. The thickness of the grain is dried in the sun need to be added so as not too thin and can produce more rice intact during milling. Entrepreneur RMU need to complete with seed cleaner to increase the yield, as well as using double-pass system so that quality and yield of rice produced would be better.